PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM KOTA PALU - Darmin, Yus (Katalogis, 2015)
This research aims to explore and analyze significant effects of leadership style, job motivation, and work environment on employees’ performance in The Department of Public Works of Palu, both simultaneously and partially. The type of the research is causal descriptive to link betwen two or more independent variables. Population consist of all employees in The Department of Public Works of Palu with 154 personel selected as sample through census sampling technique. Based on multiple linear regression analysis, the result show that leadership style, job motivation, and work environment simultaneously and partially have significant effect on the performance of employees in The Department of Public Work of Palu.